Near-infrared dye loaded polymeric nanoparticles for cancer imaging and therapy and cellular response after laser-induced heating - Lei, Tingjun; Fernandez-Fernandez, Alicia; Manchanda, Romila; Huang, Yen-Chih; McGoron, Anthony J. (Beilstein Journal of Nanotechnology, 2014)
Background: In the past decade, researchers have focused on developing new biomaterials for cancer therapy that combine imaging and therapeutic agents. In our study, we use a new biocompatible and biodegradable polymer, termed poly(glycerol malate co-dodecanedioate) (PGMD), for the synthesis of nanoparticles (NPs) and loading of near-infrared (NIR) dyes. IR820 was chosen for the purpose of imaging and hyperthermia (HT). HT is currently used in clinical trials for cancer therapy in combination with radiotherapy and chemotherapy. One of the potential problems of HT is that it can up-regulate hypoxia-inducible factor-1 (HIF-1) expression and enhance vascular endothelial growth factor (VEGF) secretion.Results: We explored cellular response after rapid, short-term and low thermal dose laser-IR820-PGMD NPs (laser/NPs) induced-heating, and compared it to slow, long-term and high thermal dose heating by a cell incubator. The expression levels of the reactive oxygen species (ROS), HIF-1 and VEGF following the two different modes of heating. The cytotoxicity of NPs after laser/NP HT resulted in higher cell killing compared to incubator HT. The ROS level was highly elevated under incubator HT, but remained at the baseline level under the laser/NP HT. Our results show that elevated ROS expression inside the cells could result in the promotion of HIF-1 expression after incubator induced-HT. The VEGF secretion was also significantly enhanced compared to laser/NP HT, possibly due to the promotion of HIF-1. In vitro cell imaging and in vivo healthy mice imaging showed that IR820-PGMD NPs can be used for optical imaging.Conclusion: IR820-PGMD NPs were developed and used for both imaging and therapy purposes. Rapid and short-term laser/NP HT, with a low thermal dose, does not up-regulate HIF-1 and VEGF expression, whereas slow and long term incubator HT, with a high thermal dose, enhances the expression of both transcription factors.
Keywords: hypoxia-inducible factor-1; IR820; nanoparticle; poly(glycerol malate co-dodecanedioate) (PGMD); vascular endothelial growth factor